Peningkatan Kemampuan Membaca Intensif melalui Penerapan Model Pembelajaran Kooperatif Investigasi Kelompok terhadap Siswa Kelas IV Sekolah Dasar - Faisal B., Muh.; Rustan, Edhy; Mirnawati, Mirnawati (South Sulawesi Education Development, 2024)
This research aims to improve the ability of intensive reading through the application of cooperative cooperative learning model of group investigation in fourth grade students of Sekolah Dasar (SD) Negeri 4 Porehu, Kec. Porehu, Kab. Kolaka Utara. Using the approach of Classroom Action Research approach, this research was conducted in two cycles, with each cycle comprising of in two cycles, with each cycle consisting of four stages: planning, action and observation, observation, and reflection. Data were collected through observation, interviews, documentation studies, and tests. The results showed that in cycle I, the cooperative learning strategy had not been successful, with some students scoring below 70% some students who scored below 70%. However, in cycle II, with maximized implementation and improved strategies, no students scored below 70%, indicating success. Students who scored below 70%, indicating the success of the strategy. This research confirms the importance of an interactive and student-centered learning approach in interactive and student-centered learning approaches in improving elementary students' intensive reading skills. Keywords: , , ,